The Influence of Corporate Social Responsibility (CSR) Disclosures on Corporate Financial Performance with Industrial Types as Moderating Variables - Ivani Juni Nainggolan; Sofik Handoyo (Universitas Padjadjaran, 2019)
This study aims to examine the effect of implementing Corporate Social Responsibility (CSR) on the company's financial performance, with the industry type as a moderating variable. CSR disclosure was measured using CSR disclosure under ISO 26000. Return on Asset is a proxy to measure the company’s financial performance. The type of industry was divided into a high profile and low-profile company. The research subjects are the leading sector companies (raw material producing industries) and the second sector (manufacturing industries) which consist of various sectors namely agriculture, mining, basic and chemical industries, various industries, and consumer goods which are listed on the Indonesia Stock Exchange in 2012-2013. Partially, the results showed that the disclosure of CSR implementation and industry type positively and significantly affected the company's financial performance, and the type of industry succeeded in becoming a moderating variable that influenced the relationship between CSR disclosure and the company's financial performance. Simultaneously, the results of the study also show that there is a significant effect of the level of disclosure of Corporate Social Responsibility (CSR) on financial performance with industry type as a moderating variable.